Analisis Pengaruh Pendidikan dan Pelatihan Struktural Terhadap Kinerja Pelayanan Birokrasi Di Lingkungan Sekretariat Daerah Kabupaten Rejang Lebong - Dhaniel, Ridianto; Hartono, Rudi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2020)
The purpose of this study was to determine and analyze: (1) Implementation of structural education and training (training) within the Rejan Lebong Regency Regional Secretariat, (2) Performance of Bureaucratic Services within the Rejang Lebong Regency Regional Secretariat, (3) Influence between education and training (training) structural with the performance of bureaucratic services within the Rejang Lebong Regency Regional Secretariat. This type of research is a descriptive analytical study. The population in this study were all civil servants / employees who had participated in structural education and training within the Rejang Lebong Regency Regional Secretariat, amounting to 48 people. The sample used in this study is a total sample. Data analysis was performed descriptively quantitative and qualitative, using the computer program SPSS Version 11.0. Before analyzing the data to test the research hypothesis, the researcher first conducted a Data Normality Test, which included: Validity Test and Reliability Test. Hypothesis testing, using statistical calculations and analysis using the T Test and Regression Analysis. The results of this study are Structural Education and Training within the Rejang Lebong Regional Secretariat in the excellent category, which was stated by 62.5% of respondents. While 37.5% of respondents stated good. The performance of bureaucratic services within the Rejang Lebong Regency Regional Secretariat is in the good category stated by 66.6% of respondents. While 33.3% of respondents stated very good. There is a significant influence between structural education and training and the performance of bureaucratic services within the Rejang Lebong Regency Regional Secretariat. This is evidenced by the results of data analysis which states that t arithmetic is greater than t table (7.943> 2.013). The results of the r count also prove that 57.8% of the performance of bureaucratic services in the Rejang Lebong Regency Regional Secretariat is influenced by the variable education and structural training. Whereas 42.2% are again influenced by other variables not yet examined in this study.